Openness and technological innovation in East Asia: have they increased the demand for skills? - Rita K. Almeida (Institute for the Study of Labor (IZA), 2009)
This paper asks whether the increased openness and technological innovation in East Asia have contributed to an increased demand for skills in the region. We explore a unique firm level data set across eight countries. Our results strongly support the idea that greater openness and technology adoption have increased the demand for skills, especially in middle income countries. Moreover, while the presence in international markets has been skill enhancing for most middle income countries, this has not been the case for manufacturing firms operating in China and in low-income countries. If international integration in the region intensifies further and technology continues to be skilled biased, policies aimed at mitigating skills shortages in the region should produce continual and persistent increases in skills.
urn:nbn:de:101:1-20091015842
Keywords: J23; J24; J31; O33; 330; Demand for skills; foreign direct investment; exports; firm level data; Technischer Fortschritt; Technologietransfer; Direktinvestition; Arbeitsnachfrage; Hochqualifizierte Arbeitskräfte; Ostasien